The Determinants of Financial Literacy, Consumptive Lifestyle and Parental Support on the Emergency Fund Formations among University Student in Makassar: English - Giauw, Alfons; Pagiling, Novieanty; Giauw, Vinshen; Tandreas, Felix; Djiemesha, Ritchie; Sumilat, Ian Thomas (Manunggal Halim Jaya, 2025)
This study explores the impact of financial literacy, consumptive, lifestyle, and parental support on the formation of emergency funds among university students in Makassar. With the rise of economic uncertainties, student’s ability to manage personal finances—especially saving for emergencies—has become increasingly important. However, many lack the financial knowledge, behavioral discipline, and external support needed to establish such reserves. Using a quantitative approach and survey data from 203 respondents, the study reveals that financial literacy and parental support positively and significantly influence emergency fund formation, while a consumptive lifestyle has a negative and significant effect. The simultaneous analysis shows that these three variables account for 51.8% of the variance in emergency fund formation behavior. These findings highlight the intertwined roles of knowledge, lifestyle habits, and family influence in shaping students’ financial preparedness. The study emphasizes the importance of targeted financial education and parental involvement to enhance students’ financial resilience, and suggests future research explore additional variables such as peer influence and digital finance tools.